No association of genetic variants in BDNF with major depression: A meta‐ and gene‐based analysis12. Issue 1 (26th November 2012) - Gyekis, Joseph P.; Yu, Weihong; Dong, Shuqian; Wang, Haina; Qian, Jun; Kota, Pravina; Yang, Jingyun
Abstract Major depressive disorder (MDD) is a complex psychiatric condition with strong genetic predisposition. The association of MDD with genetic polymorphisms, such as Val66Met (rs6265), in the brain derived neurotrophic factor (BDNF), have been reported in many studies and the results were conflicting. In this study, we performed a systematic literature search and conducted random‐effects meta‐analysis to evaluate genetic variants in BDNF with MDD. A gene‐based analysis was also conducted to investigate the cumulative effects of genetic polymorphisms in BDNF. A total of 28 studies from 26 published articles were included in our analysis. Meta‐analysis yielded an estimated odds ratio (OR) of 0.96 (95% CI: 0.89–1.05; P = 0.402) for Val66Met (rs6265), 0.83 (95% CI: 0.67–1.04; P = 0.103) for 11757C/G, 1.16 (95% CI: 0.74–1.82; P = 0.527) for 270T/C, 1.03 (95% CI: 0.18–5.75; P = 0.974) for 712A/G and 0.98 (95% CI: 0.85–1.14; P = 0.831) for rs988748. The gene‐based analysis indicated that BDNF is not associated with MDD (P > 0.21). Our updated meta‐ and novel gene‐based analyses provide no evidence of the association of BDNF with major depression. © 2012 Wiley Periodicals, Inc.